Bodies in the Classroom: Integrating Physical Literacy - Carolina Mancuso (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
This essay, based on research in Masters level classrooms for education students enrolled in a Graduate Literacy Program, addresses issues of mind-body-spirit teaching and learning..